2014
DOI: 10.1007/s11469-013-9473-y
|View full text |Cite
|
Sign up to set email alerts
|

Rating the Suitability of Responsible Gambling Features for Specific Game Types: A Resource for Optimizing Responsible Gambling Strategy

Abstract: A Delphi based study, rated the perceived effectiveness of 45 responsible gambling (RG) features in relation to 20 distinct gambling type games. Participants were 61 raters from seven countries, including responsible gambling experts (n = 22), treatment providers (n = 19) and recovered problem gamblers (n = 20). The most highly recommended RG features could be divided into three groups 1) Player initiated tools focused on aiding player's behaviour 2) RG features related to informed--player-choice 3) RG feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Theoretical and practical issues of RG have been addressed in a number of academic publications (Blaszczynski et al 2011;Blaszczynski et al 2004;Griffiths 2012;Wood et al 2014a). Blaszczynski et al (2011) described the general principles and minimal requirements of RG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and practical issues of RG have been addressed in a number of academic publications (Blaszczynski et al 2011;Blaszczynski et al 2004;Griffiths 2012;Wood et al 2014a). Blaszczynski et al (2011) described the general principles and minimal requirements of RG.…”
Section: Introductionmentioning
confidence: 99%
“…They used benchmarking to examine the extent to which the Queensland Responsible Gambling Code of Practise has been implemented. However, to date, the majority of RG staff training programs have not been tested empirically (Blaszczynski et al 2004;Wood et al 2014a). Ladouceur et al (2004) described and evaluated an awareness training program (entitled 'As luck would have it') completed by video lottery retailers in Quebec Province (Canada) and found that the program was successful in improving retailers' understanding of problem gambling and its symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been repeatedly identified that it is erroneous to consider all online gambling activities as being remotely homogenous, given the observed variation in not only the game structure but in the types of individuals that play specific games Laakusuo et al, 2014;Wood et al, 2014). At present, policy decisions surrounding online gambling - particularly in relation to problem gambling (and including problematic online poker players) - are often made by conceptualising online gambling as a single entity.…”
Section: Limitations Of Evidence Basementioning
confidence: 99%
“…Several researchers have identified that one of the most significant problems limiting the ability to implement effective responsible gambling features, is that there is an erroneous perception of 8 homogeneity across gambling activities rather than an attempt to consider the effectiveness of a combination of features in relation to a specific gambling activity, for example online poker (Gainsbury, Parke & Suhonen, 2013;Laakuso et al, 2014;Wood, Shorter & Griffiths, 2014).…”
Section: Conceptualisation Of Responsible Gambling Strategymentioning
confidence: 99%
See 1 more Smart Citation